Financial Literature Education to Increase Saving Motivation in Elementary School Students - Permana, Wegy Predy; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Indonesian Journal of Multidiciplinary Research, 2021)
Financial literacy includes the human understanding of personal financial management. Financial literacy needs to be done from an early age. The purpose of this study was to determine how big the level of understanding of elementary school students towards financial literacy and how much motivation to save elementary school students. This research was conducted by a quantitative method by producing primary data. Primary data was obtained from the activities of filling out pre-test and post-test questions to elementary school students. The results of this study indicate that many students have made a habit of saving but their level of understanding of financial literacy is still low. The results of the research show that the average post-test score of students is 88.7%, which is greater than the average pre-test score of 81.3%, so there is an increase of 7.4%. Students' understanding of financial literacy increased by 7.4% after being given a learning video. Elementary school students should build the habit of saving from now on. Saving habits make elementary school students trained in managing their finances.